2018
DOI: 10.1109/tits.2017.2766093
|View full text |Cite
|
Sign up to set email alerts
|

Point-to-Set Distance Metric Learning on Deep Representations for Visual Tracking

Abstract: Abstract-For autonomous driving application, a car shall be able to track objects in the scene in order to estimate where and how they will move such that the tracker embedded in the car can efficiently alert the car for effective collisionavoidance. Traditional discriminative object tracking methods usually train a binary classifier via a support vector machine (SVM) scheme to distinguish the target from its background. Despite demonstrated success, the performance of the SVM based trackers is limited because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Transfer learning [41][42][43] is a common approach to handle lack of training data in a dataset. It is widely believed that networks trained on the ImageNet dataset [44] are able to learn general features from it; then, this network can be fine-tuned on other datasets for a specific task such as face recognition [45,46], classification [47][48][49], detection [50,51], and visual tracking [52][53][54]. Therefore, it makes transfer learning an essential approach, especially for the small datasets.…”
Section: Transfer Learningmentioning
confidence: 99%
“…Transfer learning [41][42][43] is a common approach to handle lack of training data in a dataset. It is widely believed that networks trained on the ImageNet dataset [44] are able to learn general features from it; then, this network can be fine-tuned on other datasets for a specific task such as face recognition [45,46], classification [47][48][49], detection [50,51], and visual tracking [52][53][54]. Therefore, it makes transfer learning an essential approach, especially for the small datasets.…”
Section: Transfer Learningmentioning
confidence: 99%
“…When the training sample is nonlinear, the tracker will not be able to track the target. To address this problem, Zhang et al [3] proposed a distance-based distance learning method based on deep learning. Experiments have shown that even without model updates, the proposed method achieves favorable performance on challenging images.…”
Section: Related Workmentioning
confidence: 99%
“…In [31], a variety of usual feature extraction methods were used to combine and form new features by utilizing complementary information between features. In the research [6,7,[32][33][34][35], deep leaning (DL) was used as the extraction method of tracking algorithm and obtained great success. Wang et al [32] proposed the point-to-set distance metric learning which was conducted on convolutional neural network features of the training data extracted from the starting frames.…”
Section: The Appearance Representation In Trackingmentioning
confidence: 99%
“…In the research [6,7,[32][33][34][35], deep leaning (DL) was used as the extraction method of tracking algorithm and obtained great success. Wang et al [32] proposed the point-to-set distance metric learning which was conducted on convolutional neural network features of the training data extracted from the starting frames. Lei Qu et al [36] integrated fast histogram of oriented gradient (FHOG) and discriminative color descriptors (DD) to further boost the tracking performance.…”
Section: The Appearance Representation In Trackingmentioning
confidence: 99%